Mediating Role of Top Management Support Between Intrinsic Motivation Factors Towards Employee Engagement In Oman's Private Universities - Almamari , Maroa Khalfan; Muslim , Noor Awanis; Khudari , Mohamed (Journal of Ecohumanism, 2025)
Employee engagement has recently been a popular topic in business and management research. Current research connecting the concepts of employee motivation and engagement has focused on survey analysis and the employee perspective, investigating the factors that are important to employees in their engagement at work. This study aims to develop a deeper understanding of how top management in Oman's private universities perceives intrinsic motivation's influence on employee engagement. The study focuses on administrative employees in eight private universities in Oman, with an estimated data-gathering sample of 371. The PLS-SEM method was used to explore the relationship between the variables. According to the results, all proposed hypotheses were significantly accepted. This research contributes to the body of knowledge on employee engagement by providing empirical evidence that can be used to improve the performance of private universities in Oman. Additionally, the study's methodology can be applied by modifying the variables used to assess employee engagement improvement and success.